Pengaruh Pengeceran, Harga Grosir Dan Promosi Penjualan Terhadap Loyalitas Konsumen Mall Di Tegal - Wiyanti, Sari; El Fatin, Vinka Maulida; Solekha, Intan Haniyatus; Ahmad, Nurhaliza; Aulia, Vira (Jurnal Bisnis dan Kewirausahaan, 2022)
The conditions of high competition in the retail business require business people to maintain consumer loyalty so that consumers do not switch to their competitors. The aim of this research is to analyze the influence of Retailing, Wholesale Prices and Promotional Sales on Consumer Loyalty. The type of research used is quantitative research. The samples in this research were consumers who shopped at supermarkets, malls and modern retail stores in Tegal. The sample size was determined using the Cochran formula, namely 100 respondents. The sampling technique is non-probability sampling and sample determination is through the Accidental Sampling method. The research coefficient results for the Retail and Consumer Loyalty variables are positive at 0.192, meaning they are positively related. The value of tcount > ttable is 2.341 > 1.661 with a sig value. 0.021 < 0.05 means H1 is accepted. The variable coefficient for wholesale prices and consumer loyalty is positive at 0.356, meaning there is a positive relationship. The value of tcount > ttable is 4.034 > 1.661 with a sig value. 0.000 < 0.05 means H2 is accepted. The coefficient of the sales promotion perception variable and consumer loyalty is positive at 0.486, meaning there is a positive relationship. tcount > ttable, namely 4.175 > 1.661 with a sig value. 0.000 < 0.05, meaning H3 is accepted. The Fcount result is 35.607 with a sig value. signature. < 0.05 or 0.000 < 0.05, so H4 is accepted.